1984
DOI: 10.1002/bit.260260725
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a washed carrot preparation by cellulases and pectinases

Abstract: A washed carrot substrate, prepared with high yields and easy handling properties, was found to be a suitable substrate for studying cellulolytic and pectinolytic degradation processes. A cellulase from Trichoderma reesei, and Rohament P, a macerating enzyme from Aspergillus alleaceus in endopolygalacturonase, degraded the washed carrot substrate to an extent of 60%. With the combined action of both enzymes, degradation was more than 80%. Simultaneous action of both enzymes was more efficient than their sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…As previously reported by Voragen et al . (1980) and Sreenath et al . (1984), the results in this paper showed that a combination of pectinase and cellulase was more efficient in degrading the onion than the lone use of enzyme.…”
Section: Discussionmentioning
confidence: 97%
“…As previously reported by Voragen et al . (1980) and Sreenath et al . (1984), the results in this paper showed that a combination of pectinase and cellulase was more efficient in degrading the onion than the lone use of enzyme.…”
Section: Discussionmentioning
confidence: 97%
“…Previously fungal pectinase have been used for production of pulps, juices [22] and concentrates from fruits and vegetables and baby and geriatric foods [23]. The yield of oil extracted from olive pastes, treated by enzymatic preparation, was also increased [24].…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic effect permitted the cell walls to be more permeable, which generated the extraction of total soluble solids from the plantain puree. The presence of polysaccharide-degrading enzymes (amyloglucosidase, α-amylase, pectinase and bioglucanase activities) in the preparations was then linked to a higher degree of tissue breakdown, discharging more compounds, such as sugars [45], which contribute to total soluble solids.…”
Section: Impact Of Enzyme Concentrationmentioning
confidence: 99%